ANALISIS KESALAHAN BERBAHASA INDONESIA PADA PENULISAN CAPTION DI MEDIA SOSIAL FACEBOOK - Yulia Adiningsih; Marcel Kandiswara; Ridha Meidina Putri; Niken Novana Ayi Iskandar; Lestari Wulandari; Nurannisa Komara (Jurnal Fascho: Kajian Pendidikan dan Sosial Kemasyarakatan, 2023)
Facebook is one of the most popular social media and one of the free social media that can be used by all groups. Language errors are often found in social interaction activities on social media. This study aims to explain Indonesian language errors in writing Facebook captions. The method used is descriptive qualitative to describe the phenomena obtained in accordance with the actual situation in the field. The data collection technique is by looking at the document study notes. The data analysis technique used in this research is data reduction analysis to process the research data that has been collected. The results of the study revealed that errors in Indonesian were still found in the use of punctuation, spelling and the use of capital letters.